Chappie [videorecording (DVD)] - Jackman, Hugh; Weaver, Sigourney, 1949-; Copley, Sharlto, 1973-
In the near future, crime is patrolled by an oppressive mechanized police force. But now, the people are fighting back. When one police droid, Chappie, is stolen and given new programming, he becomes the first robot with the ability to think and feel for himself. As powerful, destructive forces start to see Chappie as a danger to mankind and order, they will stop at nothing to maintain the status quo and ensure that Chappie is the last of his kind.